Yemeni Resistance Against the Ottomans Occupation in the Sixth Century: Historical Reasons-Based study - Nasr, Ali Ahmed (Journal of Humanities & Social Sciences, 2019)
This study approaches the reasons and motives that drove Yemeni people to resist the first othmanian existence in Yemen. It is needless to say that there were many reasons, be they political or economic. Political reasons were such as, assassination, looting, levying and repression. While economic reasons were represented in diversity through which the people suffer such as, drought, desertification and floods. In addition to currency false fabrication exacerbated the situation. All that factors led eventually to the resistance of this foreign existence.
Keywords: resistance; Ottomans; causes; Yemen